DESIGN SENSITIVITY ANALYSIS AND PERFORMANCE IMPROVEMENT OF A SIX-PHASE SQUIRREL-CAGE INDUCTION MACHINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
Current research increasingly focuses on improving the design of six-phase induction motors, particularly within the realm of scientific inquiry. The primary objectives of this study include maximizing motor efficiency while minimizing losses, decreasing motor mass, maximizing power output within a compact size, addressing environmental concerns such as vibrations, acoustic noise, electromagnetic compatibility, and incorporating eco-friendly materials. This paper investigates the design sensitivity analysis and performance improvement of six-phase asynchronous motors under investigation. To achieve this goal, design parameter variations are performed to analyze their influence on machine characteristics, geometric and electrical parameters, aiming to minimize losses and motor size while maximizing efficiency. This approach endeavors to create robust and dependable machines while minimizing associated costs.
Keywords: Efficiency; Loss minimization; Motor mass reduction; Optimization; Performance enhancement; Power output maximization; Reliability; Six-phase induction motor